2008
DOI: 10.1037/0021-9010.93.3.665
|View full text |Cite
|
Sign up to set email alerts
|

Keeping up with the Joneses: A field study of the relationships among upward, lateral, and downward comparisons and pay level satisfaction.

Abstract: The authors examined the relationship between the direction of pay comparisons and pay level satisfaction. They hypothesized that upward pay comparisons would significantly predict pay level satisfaction, even when controlling for other comparisons. Results reported in 2 samples (U.S. sample, N ϭ 295; Belgian sample, N ϭ 67) generally supported this hypothesis. Analyses showed that individuals who were paid much less than their upward pay comparison were dissatisfied with their pay level. The highest levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 63 publications
2
94
0
Order By: Relevance
“…In examining the polynomial regression results, less emphasis has been placed on the specific beta coefficients (Edwards, 2002;Harris, Anseel, & Lievens, 2008). If the variance explained by the regression equation is significantly different from zero, the beta coefficients can be used to graph the response surface pattern and to calculate four values to test specific aspects of the surface (Edwards, 2001;Shanock, Baran, Gentry, Pattison, & Heggestad, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In examining the polynomial regression results, less emphasis has been placed on the specific beta coefficients (Edwards, 2002;Harris, Anseel, & Lievens, 2008). If the variance explained by the regression equation is significantly different from zero, the beta coefficients can be used to graph the response surface pattern and to calculate four values to test specific aspects of the surface (Edwards, 2001;Shanock, Baran, Gentry, Pattison, & Heggestad, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In general, most people believe that they are above-average performers (e.g., Alicke, Klotz, Breitenbecher, Yurak & Vredenburg, 1995) and should be rewarded for their performance (Gomes-Mejia & Welbourne, 1991); consequently, they are sensitive to pay increases and the process used to allocate pay increases (Harris, Anseel & Lievens, 2008). Thus, the extent to which procedures used to allocate pay increases are perceived to be fair is likely to be positively related to satisfaction with pay raises.…”
Section: Procedural Justice and Satisfaction With Pay Componentsmentioning
confidence: 99%
“…When pay is secret, employees tend to overestimate the pay of those both at their same level and below and underestimate the pay of those above them (Milkovich & Anderson, 1972). Research has shown that people are more apt to engage in upward comparisons (compare oneself with someone making more) than lateral or downward comparisons (Harris, Anseel & Lievens, 2008). Given that most people believe that they are above-average performers (e.g., Alicke et al, 1995), they are likely to feel that their performance and contributions warrant a higher pay increase than what they receive, and thus feel the outcome to be somewhat unfavorable.…”
Section: Interpersonal Justice and Satisfaction With Pay Componentsmentioning
confidence: 99%
“…Those high in the internal pay structure (overpayment) did not report discomfort, but rather reported about the same level of satisfaction as those equitably paid, as typical equity theory studies tend to report. Harris et al (2008) also examined upward and downward pay comparisons and satisfaction in two experimental settings. They found that pay-level satisfaction was lowest when participant pay levels fell short of upward comparators, increased to high levels as pay matched that of upward comparators, and then declined slightly in overpayment situations.…”
Section: Pay Dispersion and Attitudesmentioning
confidence: 99%